SETS Best Practice Model: Growth Optimization and Productivity of Organic Food Plants through IASMUSPEC Application - Rosana, D.; Kadarisman, N.; Suryadarma, I. G. P. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
The application of SETS (Science, Technology, Environment, and Society) approach through the Biophysics course has been proven as an effective solution to develop new literacy among students of Natural Sciences Study Program, Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta. The application of this approach can solve the students’ learning difficulties in connecting SETS elements within learning by providing integrated technology that is in line with basic competencies and learning indicators. The relational model of Integrated Audio Stimulator - Multi-Sensor - Pest Control (IASMUSPEC) engineering to optimize the growth and productivity of organic food plants directly involve students in practical science learning by applying technology to assist farmers. The method to produce SETS best practice model was the combination of Research & Development of spiral model referring to Cennamo and Kalk concept (2018) and Experimental Research for implementing IASMUSPEC to increase organic food plants productivity. A preliminary study of this research results in two aspects. They are the skills improvement aspect for both students and farmers in applying IASMUSPEC, and the increase of productivity aspect in organic rice plants into 209.81% (yield total for land samples of 8.3 x 29.8 meters) in the treatment plants was 237.3 kg, with and for control plants was 113.1 kg respectively. The effects of IASMUSPEC on plant growth rates were also examined. The output of this study was the subject-specific pedagogic (SSP) of Biophysics with SETS approach and IASMUSPEC appropriate technology.